Green Silver Nanoparticles Formed by Phyllanthus urinaria, Pouzolzia zeylanica, and Scoparia dulcis Leaf Extracts and the Antifungal Activity - Nguyen, Dai Hai (Nanomaterials (Basel), 2020)
Phytoconstituents presenting in herbal plant broths are the biocompatible, regenerative, and cost-effective sources that can be utilized for green synthesis of silver nanoparticles. Different plant extracts can form nanoparticles with specific sizes, shapes, and properties. In the study, we prepared silver nanoparticles (P.uri.AgNPs, P.zey.AgNPs, and S.dul.AgNPs) based on three kinds of leaf extracts (Phyllanthus urinaria, Pouzolzia zeylanica, and Scoparia dulcis, respectively) and demonstrated the antifungal capacity. The silver nanoparticles were simply formed by adding silver nitrate to leaf extracts without using any reducing agents or stabilizers. Formation and physicochemical properties of these silver nanoparticles were characterized by UV-vis, Fourier transforms infrared spectroscopy, scanning electron microscope, transmission electron microscope, and energy dispersive X-ray spectroscopy. P.uri.AgNPs were 28.3 nm and spherical. P.zey.AgNPs were 26.7 nm with hexagon or triangle morphologies. Spherical S.dul.AgNPs were formed and they were relatively smaller than others. P.uri.AgNPs, P.zey.AgNPs and S.dul.AgNPs exhibited the antifungal ability effective against Aspergillus niger, Aspergillus flavus, and Fusarium oxysporum, demonstrating their potentials as fungicides in the biomedical and agricultural applications.